5-8x=13+7(x-3)

Simple and best practice solution for 5-8x=13+7(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-8x=13+7(x-3) equation:


Simplifying
5 + -8x = 13 + 7(x + -3)

Reorder the terms:
5 + -8x = 13 + 7(-3 + x)
5 + -8x = 13 + (-3 * 7 + x * 7)
5 + -8x = 13 + (-21 + 7x)

Combine like terms: 13 + -21 = -8
5 + -8x = -8 + 7x

Solving
5 + -8x = -8 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
5 + -8x + -7x = -8 + 7x + -7x

Combine like terms: -8x + -7x = -15x
5 + -15x = -8 + 7x + -7x

Combine like terms: 7x + -7x = 0
5 + -15x = -8 + 0
5 + -15x = -8

Add '-5' to each side of the equation.
5 + -5 + -15x = -8 + -5

Combine like terms: 5 + -5 = 0
0 + -15x = -8 + -5
-15x = -8 + -5

Combine like terms: -8 + -5 = -13
-15x = -13

Divide each side by '-15'.
x = 0.8666666667

Simplifying
x = 0.8666666667

See similar equations:

| 5=8n-7n | | -23k+63=-45 | | 6(1d-4)=4d-18 | | 4(x-5)-2x=4 | | 1=2x-3x | | 8a+32=8a | | -134=20x-34 | | 15+w=8 | | 2(x-5)=8x-5 | | 3(n+2)+5=6(n+4)+n | | -4s+2l=50 | | 5(2x+1)=3(3x-2) | | 7x-2(3x+5)=2 | | (3x-1)=3+8x-11 | | 6x=5(x-2) | | 4(-11)+x(3x-4)-6(x+6)=y | | 78=-2m+6+m | | 2(3x-4)=5x-6 | | 3x-1=-8+8x | | 3x-33=15 | | 7x+25=235 | | 122+32+n=180 | | -1x+4=8.0 | | =19-15(-9+17k) | | 8-81+-2n=-75 | | x+3=-x+7 | | -5x+10=2x+31 | | 7+25x=235 | | 6=-x+4x | | 3x+5x-10=10x+5x+10-20 | | 1200-870-30x=11 | | 13x^2y^2+39x^4y= |

Equations solver categories